Alternative models of waqf-based takaful products for flood victims in Malaysia: an assessment from practitioners’ perspectives - Che Mohd Salleh, Marhanum; Kassim, Salina; Razali, Siti Salwani; Che Embi, Nor Azizan; Megat Laksana, Nan Noorhidayu (IIUM Press, International Islamic University Malaysia, 2018)
Disastrous flood has becoming an increasing concern in Malaysia especially at the end of every calendar year. This calamity has negatively affected many aspects of life of the flood victims, resulting in substantial financial losses to them. This research aims to propose three models of Takaful products based on Waqf principle in efforts to provide financial protection for the flood victims. Focus group discussions have been conducted with industry players, namely Takaful operators, bankers, government agencies, and Islamic state of religious councils to obtain their views on the three models being proposed in the research. Based on the discussion, the third model which involves multi-sources multi-usages of waqf-based Takaful model is the most viable and sustainable in view of the diversified sources of funds. Results of this research would assist the government and industry players to come out with new Takaful products based on waqf principle that may enhance the roles of all parties in the society to indoctrinate the unity spirit. Ultimately, it may help to reduce the financial burden of the government especially in terms of expenses during the flood season as well as assisting the victims for their financial constraints.